Aqueous dispersion, method for manufacturing laminate, laminate, metal-clad laminate, and on-vehicle radar
The aqueous dispersion, comprising hot-melt tetrafluoroethylene polymer particles and high specific gravity inorganic fillers, addresses the challenge of uniform dispersion and adhesion in resin layers, achieving excellent adhesion and physical properties in laminate formations.
Patent Information
- Application Number
- JP2023173117
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-04
- Publication Date
- 2025-04-16
AI Technical Summary
High-dielectric fillers with high specific gravity are difficult to uniformly disperse in aqueous dispersions containing tetrafluoroethylene polymer particles, leading to settling, uneven distribution, and reduced liquid physical properties, which in turn affects the adhesion of the resin layer formed on substrates.
An aqueous dispersion comprising hot-melt tetrafluoroethylene polymer particles, an inorganic filler with an average particle diameter of less than 10 μm and specific gravity of 3.0 or more, and water, with a mass ratio of the inorganic filler to the polymer particles less than 1, and a surface tension of less than 50 mN/m, which improves dispersion stability and adhesion.
The aqueous dispersion effectively forms a resin layer with excellent adhesion, ensuring uniformity and improved physical properties, even when applied to substrates like nonwoven sheets.
Smart Images

Figure 2025063712000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an aqueous dispersion, a method for producing a laminate, a laminate, a metal-clad laminate, and an on-vehicle radar. [Background technology]
[0002] Tetrafluoroethylene-based polymers are useful as insulating materials in high-frequency printed circuit boards due to their excellent electrical properties. Various materials have been proposed as such insulating materials, including materials having a laminated structure and materials combined with different materials such as inorganic fillers. Patent Document 1 describes a dielectric material including a first adhesive layer, a first core layer, and an optional second adhesive layer, each having a specific thickness; and a copper-clad laminate using the same. It also describes that the first core layer is composed of a tetrafluoroethylene-based polymer modified with an inorganic filler. Patent Document 2 describes a resin composition containing an elastomer, a tetrafluoroethylene-based polymer filler, and an inorganic filler, as well as a metal laminate and a printed circuit board using the same. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2023-002495 A [Patent Document 2] Special Publication No. 2022-514976 Summary of the Invention [Problem to be solved by the invention]
[0004] In insulating materials containing tetrafluoroethylene-based polymers, fillers with high dielectric constants such as TiO2 may be blended into the insulating material in order to adjust the dielectric constant while maintaining a low dielectric loss tangent. However, such high dielectric fillers generally have a high specific gravity and are difficult to uniformly disperse in the insulating material. In particular, the present inventors have found that when the insulating material is an aqueous dispersion containing particles of tetrafluoroethylene-based polymers, such high dielectric fillers tend to settle or be unevenly distributed, and the liquid properties of the aqueous dispersion tend to be significantly reduced. The present inventors have also found that when such an aqueous dispersion is applied to a substrate or the like to form a resin layer, it becomes difficult to form a uniform resin layer, which reduces the adhesion to the adherend. In view of the above circumstances, the present disclosure relates to providing an aqueous dispersion capable of forming a resin layer having excellent adhesion, a laminate having a resin layer having excellent adhesion and a manufacturing method thereof, and a metal-clad laminate and an on-board radar using the same. [Means for solving the problem]
[0005] Means for solving the above problems include the following aspects. <1> An aqueous dispersion comprising particles of a heat-fusible tetrafluoroethylene-based polymer in an amount of 10% by mass or more relative to the aqueous dispersion, an inorganic filler having an average particle size of less than 10 μm and a specific gravity of 3.0 or more, and water, wherein the mass ratio of the inorganic filler to the particles of the heat-fusible tetrafluoroethylene-based polymer is less than 1, and the surface tension is 50 mN / m or less. <2> The heat-meltable tetrafluoroethylene-based polymer contains a unit based on tetrafluoroethylene and at least one of a unit based on perfluoro(alkyl vinyl ether) and a unit based on hexafluoropropylene. <1> The aqueous dispersion according to claim 1. <3> The inorganic filler is TiO2 particles. <1> or <2> The aqueous dispersion according to claim 1. <4> The viscosity at 25°C is 10,000 mPa·s or less. <1> ~ <3> 13. The aqueous dispersion according to claim 12 . <5> The thixotropy ratio calculated by dividing the viscosity η1 measured at a rotation speed of 30 rpm by the viscosity η2 measured at a rotation speed of 60 rpm is 6 or less. <1> ~ <4> 13. The aqueous dispersion according to claim 12 . <6> On the surface of the substrate <1> ~ <5> 10. A method for producing a laminate, comprising: applying the aqueous dispersion according to any one of 1 to 3; heating to remove the water; and further heating to melt and sinter the particles of the heat-fusible tetrafluoroethylene-based polymer to form a resin layer. <7> The thickness of the resin layer is 20 μm or less. <6> A method for producing the laminate described in claim 1. <8> The substrate is a nonwoven sheet. <6> or <7> A method for producing the laminate described in claim 1. <9> The nonwoven sheet comprises polytetrafluoroethylene. <8> A method for producing the laminate described in claim 1. <10> The nonwoven sheet contains an inorganic filler, and the inorganic filler contains SiO2 particles. <8> or <9> A method for producing the laminate described in claim 1. <11> A laminate comprising: a layer S containing polytetrafluoroethylene and an inorganic filler; and a layer T containing a heat-fusible tetrafluoroethylene-based polymer and an inorganic filler having an average particle size of less than 10 μm and a specific gravity of 3.0 or more, wherein the ratio of the thickness of layer S to the thickness of layer T is 2 to 50, and the total thickness is 50 to 500 μm. <12> The inorganic filler in the layer S is SiO2 particles, and the inorganic filler in the layer T is TiO2 particles. <11> The laminate according to claim 1. <13> The average particle size of the inorganic filler in the layer S is larger than the average particle size of the inorganic filler in the layer T. <11> or <12> The laminate according to claim 1. <14> <11> ~ <13> 13. A metal clad laminate comprising: the laminate according to claim 12; and a metal layer. <15> <11> ~ <13> 13. An on-vehicle radar comprising a circuit board including the laminate according to claim 12 and a conductor layer. Effect of the Invention
[0006] According to the present disclosure, there are provided an aqueous dispersion capable of forming a resin layer having excellent adhesion, a laminate having a resin layer having excellent adhesion and a manufacturing method thereof, and a metal clad laminate and an on-vehicle radar using the same. [Brief description of the drawings]
[0007] [Figure 1] FIG. 2 is a schematic diagram of a laminate in one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, the form for carrying out the embodiment of the present disclosure will be described in detail. However, the embodiment of the present disclosure is not limited to the following embodiment. In the following embodiment, the components (including element steps, etc.) are not essential unless specifically stated. The same applies to the numerical values and their ranges, and they do not limit the embodiment of the present disclosure.
[0009] In the present disclosure, the term "step" includes not only a step that is independent of other steps, but also a step that cannot be clearly distinguished from other steps as long as the purpose of the step is achieved. In the present disclosure, a numerical range indicated using "~" includes the numerical values before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples. In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In the present disclosure, each component may contain multiple types of the corresponding substance. When multiple substances corresponding to each component are present in the composition, the content or amount of each component means the total content or amount of the multiple substances present in the composition, unless otherwise specified. In the present disclosure, multiple types of particles corresponding to each component may be included. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component means the value for a mixture of the multiple types of particles present in the composition, unless otherwise specified. In the present disclosure, the terms "layer" and "film" include cases where the layer or film is formed over the entire area when the area in which the layer or film is present is observed, as well as cases where the layer or film is formed over only a portion of the area. In this disclosure, the term "lamination" refers to stacking layers, where two or more layers may be bonded together or two or more layers may be removable. In the present disclosure, a "unit" in a polymer means an atomic group based on a monomer formed by polymerization of the monomer. The unit may be a unit formed directly by a polymerization reaction, or may be a unit in which a part of the unit is converted into a different structure by treating the polymer. Hereinafter, a unit based on monomer a is also simply referred to as a "monomer a unit." In this disclosure, the "melting temperature" of a tetrafluoroethylene-based polymer is the temperature corresponding to the maximum value of the melting peak of the polymer measured by differential scanning calorimetry (DSC). In the present disclosure, the "melt flow rate" of a tetrafluoroethylene-based polymer means the melt mass flow rate of the polymer as defined in JIS K 7210-1:2014 (ISO1133-1:2011). In the present disclosure, the "glass transition temperature (Tg)" of a tetrafluoroethylene-based polymer is a value measured by analyzing the polymer by dynamic mechanical analysis (DMA). In this disclosure, the average particle size of the particles means the volume average particle size (D50), and It is the volume-based cumulative 50% diameter of a particle obtained by the laser diffraction / scattering method. In other words, the particle size distribution is measured by the laser diffraction / scattering method, the total volume of the particle group is set to 100%, and a cumulative curve is obtained, and the D50 is the particle diameter at the point on the cumulative curve where the cumulative volume is 50%. The D50 of a particle is obtained by dispersing the particles in water and analyzing them by the laser diffraction / scattering method using a laser diffraction / scattering type particle size distribution analyzer (for example, the Beckman Coulter Laser Diffraction / Scattering Particle Size Distribution Analyzer "LS-13 320"). In the present disclosure, the "specific surface area" is a value calculated by measuring particles by a gas adsorption (constant volume method) BET multipoint method, and is determined using a BET specific surface area measurement device (for example, NOVA4200e (manufactured by Quantachrome Instruments)). In the present disclosure, the "viscosity" of the aqueous dispersion is determined by measuring the aqueous dispersion using a Brookfield viscometer at 25° C. and a rotation speed of 30 rpm. The measurement is repeated three times, and the average value of the three measured values is used. In the present disclosure, the "thixotropy ratio" of an aqueous dispersion is a value calculated by dividing the viscosity η1 of the aqueous dispersion measured at a rotation speed of 30 rpm by the viscosity η2 measured at a rotation speed of 60 rpm. Each viscosity measurement is repeated three times, and the average value of the three measured values is used. In the present disclosure, the "surface tension" of an aqueous dispersion is measured by the Wilhelmy method using a surface tensiometer for the aqueous dispersion at 25°C. When an embodiment of the present disclosure is described with reference to drawings, the configuration of the embodiment is not limited to the configuration shown in the drawings. In addition, the sizes of components in the drawings are conceptual, and the relative relationships between the sizes of the components are not limited to these.
[0010] The aqueous dispersion of the present disclosure contains particles of a heat-fusible tetrafluoroethylene-based polymer in an amount of 10% by mass or more relative to the aqueous dispersion, an inorganic filler having an average particle size of less than 10 μm and a specific gravity of 3.0 or more, and water, the mass ratio of the inorganic filler to the F particles is less than 1, and the surface tension is 50 mN / m or less. Hereinafter, the heat-fusible tetrafluoroethylene-based polymer is also referred to as "F polymer", and the particles of the heat-fusible tetrafluoroethylene-based polymer are also referred to as "F particles". In addition, the inorganic filler having a specific gravity of 3.0 or more is also referred to as "high-specific-gravity inorganic filler".
[0011] It has been found that the aqueous dispersion of the present disclosure can form a resin layer with excellent adhesiveness. In the aqueous dispersion of the present disclosure, since both the F particles and the high specific gravity inorganic filler are highly hydrophobic, the interaction between the hydrophobic substances is relatively easily promoted. In other words, both can be considered to be in a state in which they are loosely likely to aggregate. In addition, the surface tension of the aqueous dispersion is below a predetermined range, which improves the wettability of the F particles and enhances their dispersibility in liquid. In other words, it is considered that the high specific gravity inorganic filler in the aqueous dispersion of the present disclosure is in a state in which the dispersion stability is easily improved by the interaction with the F particles, which are contained in a predetermined amount or more and have enhanced dispersibility in liquid. And, it is considered that such a state is further promoted by the fact that the high specific gravity inorganic filler has a particle diameter below a predetermined range, its surface area is sufficiently large, and its content is less than the content of the F particles. As a result, an aqueous dispersion (aqueous dispersion of the present disclosure) in which even the high specific gravity inorganic filler is well dispersed is formed, and a uniform resin layer can be formed from it, and the adhesiveness of the resin layer is also improved.
[0012] The F polymer contained in the F particles is a polymer containing units (hereinafter also referred to as "TFE units") based on tetrafluoroethylene (hereinafter also referred to as "TFE units"). From the viewpoint of favorably expressing the characteristics due to the TFE units, the content of the TFE units in the F polymer is preferably 50 mol% or more, more preferably 90 mol% or more, based on the total units in the F polymer. The content may be 99 mol% or less, or 98 mol% or less.
[0013] F polymer is heat-fusible. A heat-fusible polymer is one that melts and flows under a load of 49N. This means that there exists a temperature at which the coefficient of friction is 1 to 1000 g / 10 min. From the viewpoint of heat resistance, the melting temperature of the F polymer is preferably 200° C. or higher, more preferably 260° C. or higher. From the viewpoint of ease of processing, the melting temperature of the F polymer is preferably 325° C. or lower, more preferably 320° C. or lower.
[0014] From the viewpoint of heat resistance, the glass transition point of the F polymer is preferably 50° C. or higher, and more preferably 75° C. or higher. From the viewpoint of ease of processing, the glass transition point of the F polymer is preferably 150° C. or lower, and more preferably 125° C. or lower. The fluorine content of the F polymer is preferably 70% by mass or more, more preferably 72 to 76% by mass, from the viewpoint of favorable expression of properties due to fluorine atoms, such as electrical properties and heat resistance. The surface tension of the F polymer is preferably 16 to 26 mN / m. The surface tension of the F polymer can be measured by placing a droplet of a wettability index reagent (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) on a flat plate made of the F polymer.
[0015] F polymer is preferably polytetrafluoroethylene (PTFE), a polymer containing TFE unit and a unit based on ethylene, a polymer containing TFE unit and a unit based on propylene, a polymer containing TFE unit and a unit based on perfluoro(alkyl vinyl ether) (PAVE) (PAVE unit) (PFA), and a polymer containing TFE unit and a unit based on hexafluoropropylene (FEP), more preferably a polymer containing TFE unit and at least one of PAVE unit and unit based on hexafluoropropylene, more preferably PFA and FEP, more preferably PFA from the viewpoint of properties such as adhesiveness and processability.These polymers may further contain units based on other comonomers. PAVE is preferably CF2=CFOCF3, CF2=CFOCF2CF3 or CF2=CFOCF2CF2CF3 (hereinafter also referred to as "PPVE"), and more preferably PPVE.
[0016] In particular, from the viewpoint of obtaining an aqueous dispersion with high uniform dispersibility and improving the adhesion of the resin layer obtained therefrom, the F polymer preferably has an oxygen-containing polar group, more preferably has a hydroxyl group-containing group or a carbonyl group-containing group, and even more preferably has a carbonyl group-containing group.
[0017] The hydroxyl-containing group is preferably a group containing an alcoholic hydroxyl group, more preferably -CF2CH2OH or -C(CF3)2OH. The carbonyl group-containing group is preferably a carboxyl group, an alkoxycarbonyl group, an amide group, an isocyanate group, a carbamate group (-OC(O)NH2), an acid anhydride residue (-C(O)OC(O)-), an imide residue (-C(O)NHC(O)-, etc.) or a carbonate group (-OC(O)O-), and more preferably an acid anhydride residue.
[0018] When the F polymer has a carbonyl group-containing group, the number of carbonyl group-containing groups in the F polymer is 1×10 6 The number of carbonyl-containing groups per unit is preferably 10 to 5000, more preferably 100 to 3000. The number of carbonyl-containing groups in the F polymer can be quantified by the composition of the polymer or the method described in WO 2020 / 145133. The carbonyl group-containing group may be contained in a unit based on a monomer in the F polymer, or may be contained in a terminal group of the main chain of the F polymer, the former being preferred. Examples of the latter include an F polymer having a carbonyl group-containing group as a terminal group derived from a polymerization initiator, a chain transfer agent, etc., and an F polymer obtained by subjecting an F polymer to plasma treatment or ionizing radiation treatment.
[0019] The monomers having a carbonyl group-containing group are itaconic anhydride, citraconic anhydride and 5- Norbornene-2,3-dicarboxylic anhydride (hereinafter also referred to as "NAH") is preferred, and NAH is more preferred.
[0020] The F polymer is preferably a polymer having a carbonyl group-containing group containing TFE units and PAVE units, more preferably a polymer containing TFE units, PAVE units, and units based on a monomer having a carbonyl group-containing group, and containing these units in this order, 90 to 99 mol%, 0.99 to 9.97 mol%, and 0.01 to 3 mol%, based on all units. Specific examples of such F polymers include polymers described in WO 2018 / 016644.
[0021] The F particles are particles of an F polymer, preferably consisting mainly of an F polymer, and preferably consisting of an F polymer. The term "mainly consisting of an F polymer" means that the content of the F polymer is relatively high compared to the content of each of the other components on a volume basis.
[0022] From the viewpoint of dispersion stability, the D50 of the F particles is preferably 0.1 μm or more, more preferably more than 0.3 μm, and even more preferably 1 μm or more. From the viewpoint of dispersion stability, the D50 of the F particles is preferably 25 μm or less, more preferably 10 μm or less, even more preferably 8 μm or less, and particularly preferably 5 μm or less. The specific surface area of F particles is 1 to 25 m 2 / g is preferred.
[0023] F particles may be used alone or in combination of two or more. When two or more types of F particles are used in combination, different F particles refer to F particles that differ in average particle size, type of F polymer, content of F polymer, presence or absence of other components other than F polymer, content of other components, or combinations thereof.
[0024] The content of F particles in the aqueous dispersion is 10% by mass or more, and from the viewpoint of favorably imparting the properties of the F polymer, it is preferably 15% by mass or more, more preferably 20% by mass or more, and even more preferably 25% by mass or more. Also, from the viewpoint of dispersion stability, the content of F particles in the aqueous dispersion is preferably 50% by mass or less, and more preferably 40% by mass or less.
[0025] The aqueous dispersion contains a high-density inorganic filler having an average particle size of less than 10 μm. The specific gravity of the high-density inorganic filler is 3.0 or more, and may be 3.5 or more or 4.0 or more depending on the desired properties of the high-density inorganic filler. From the viewpoint of dispersibility of the aqueous dispersion, the specific gravity of the high-density inorganic filler is preferably 10.0 or less, more preferably 9.0 or less, and even more preferably 8.0 or less.
[0026] High density inorganic fillers include barium titanate (BaTiO3), strontium titanate (SrTiO3), calcium titanate (CaTiO3), magnesium titanate (MgTiO3), barium strontium titanate (SrBaTiO3), and sodium barium niobate (NaBa2Nb5O 15 ), potassium barium niobate (KBa2Nb5O 15 ), calcium zirconate (CaZrO3), titanite (CaTiSiO5), titanium dioxide (TiO2), tantalum pentoxide (Ta2O5), hafnium dioxide (HfO2), niobium pentoxide (Nb2O5), alumina (Al2O3), zinc oxide (ZnO), cerium oxide (CeO2), magnesium oxide (MgO), beryllia, and other particles. The high-density inorganic filler may be used alone or in combination of two or more kinds. Among these, metal oxides are preferred, and TiO2 particles are more preferred. At least a part of the surface of the high specific gravity inorganic filler is preferably treated with a silane coupling agent.
[0027] The average particle size of the high-density inorganic filler is less than 10 μm, and from the viewpoint of dispersibility, it is preferably 8 μm or less, more preferably 5 μm or less, and even more preferably 1 μm or less. From the viewpoint of dispersibility, the average particle size of the inorganic filler is preferably 0.01 μm or more, more preferably 0.1 μm or more, and even more preferably 0.2 μm or more. In one embodiment, a high-density inorganic filler having an average particle size of 0.5 μm or less and a high-density inorganic filler having an average particle size of more than 1.0 μm may be used in combination. By using high-density inorganic fillers having different average particle sizes in combination, the dispersibility of the high-density inorganic filler is improved, making it easier to form a resin layer. In one embodiment, TiO2 particles having an average particle size of 0.5 μm or less and TiO2 particles having an average particle size of more than 1.0 μm may be used in combination.
[0028] The shape of the high specific gravity inorganic filler is not particularly limited, and examples thereof include spherical, needle-like (fibrous), scale-like, layered, leaf-like, apricot kernel-like, columnar, cockscomb-like, equiaxed, leaf-like, micaceous, block-like, flat, wedge-like, rosette-like, mesh-like, and rectangular column-like shapes.
[0029] The content of the high-density inorganic filler is preferably 1% by mass or more, more preferably 5% by mass or more, based on the total amount of the aqueous dispersion. The content is preferably less than 30% by mass, more preferably 20% by mass or less, based on the total amount of the aqueous dispersion. When two or more kinds of high-density inorganic fillers are contained in the aqueous dispersion, the content is the total content of the two or more kinds of high-density inorganic fillers.
[0030] The mass ratio of the high-density inorganic filler to the total mass of the F particles is less than 1, and from the viewpoint of dispersibility of the high-density inorganic filler, it is preferably 0.8 or less, more preferably 0.6 or less. From the viewpoint of satisfactorily exhibiting the properties of the high-density inorganic filler, such as electrical properties (ferroelectricity, etc.), the mass ratio of the high-density inorganic filler to the total mass of the F particles is preferably 0.1 or more, more preferably 0.2 or more.
[0031] The aqueous dispersion may or may not contain an inorganic filler other than the high specific gravity inorganic filler. The mass ratio of the inorganic filler other than the high-density inorganic filler to the high-density inorganic filler is preferably 1 or less, more preferably 0.8 or less, and even more preferably 0.6 or less.
[0032] Inorganic fillers other than high specific gravity inorganic fillers (i.e., inorganic fillers having a specific gravity of less than 3.0) include boron nitride fillers, silicate fillers (silica fillers, wollastonite fillers, talc fillers), etc. Inorganic fillers having a specific gravity of less than 3.0 may be used alone or in combination of two or more. The amount of the inorganic filler having a specific gravity of less than 3.0 is preferably 50% by mass or less, more preferably 30% by mass or less, and even more preferably 10% by mass or less, based on the total mass of the inorganic filler.
[0033] When the aqueous dispersion contains an inorganic filler having a specific gravity of less than 3.0, it is preferable that at least a part of the surface of the inorganic filler is treated with a silane coupling agent. Examples of the silane coupling agent are as described above.
[0034] The total content of the inorganic filler in the aqueous dispersion is preferably from 1 to 50% by mass, more preferably from 5 to 40% by mass.
[0035] The aqueous dispersion uses water as a dispersion medium. The content of water can be appropriately adjusted in consideration of the coating method, the thickness of the resin layer to be produced, etc., and is preferably 40% by mass or more, more preferably 50% by mass or more, and even more preferably 55% by mass or more, based on the total amount of the aqueous dispersion. The content of water is preferably 90% by mass or less, more preferably 80% by mass or less, based on the total amount of the aqueous dispersion.
[0036] The aqueous dispersion may further contain a water-soluble dispersion medium other than water as a dispersion medium. The water-soluble dispersion medium is preferably a water-soluble compound that is liquid at 25° C. under atmospheric pressure and classified as polar, and examples of the water-soluble dispersion medium include N,N-dimethylformamide, N,N-dimethylacetamide, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide, and N-methyl-2-pyrrolidone.
[0037] The solid content concentration in the aqueous dispersion is preferably 20% by volume or more, more preferably 40% by volume or more, based on the total volume of the aqueous dispersion. The solid content concentration is preferably 60% by volume or less. The solid content means the total amount of substances that form the solid content in a molded product formed from the aqueous dispersion. Specifically, the F particles and inorganic filler are included in the solid content, and when the aqueous dispersion contains other resins, the other resins are also included in the solid content.
[0038] The aqueous dispersion may contain a resin other than the fluororesin. The inorganic filler may be contained in the form of powder particles or may be dissolved or dispersed in water. Examples of the other resin include polyester resins such as liquid crystalline aromatic polyesters, imide resins, epoxy resins, maleimide resins, urethane resins, polyphenylene ether resins, polyphenylene oxide resins, and polyphenylene sulfide resins. The other resins are preferably aromatic polymers, and more preferably at least one aromatic imide polymer selected from the group consisting of aromatic polyimides, aromatic polyamic acids, aromatic polyamideimides, and aromatic polyamideimide precursors. The aromatic polymer is preferably contained in the aqueous dispersion as a varnish dissolved in water. Specific examples of aromatic imide polymers include the "UPIA-AT" series (manufactured by Ube Industries, Ltd.), the "NEOPLUMI (registered trademark)" series (manufactured by Mitsubishi Gas Chemical Company, Inc.), the "SPIXELIA (registered trademark)" series (manufactured by Somar), the "Q-PILON (registered trademark)" series (manufactured by PI Technical Research Institute, Ltd.), the "WINGO" series (manufactured by Wingo Technology Co., Ltd.), the "TOMAID (registered trademark)" series (manufactured by T&K TOKA Corporation), the "KPI-MX" series (manufactured by Kawamura Sangyo Co., Ltd.), and "HPC-1000" and "HPC-2100D" (both manufactured by Showa Denko Materials Co., Ltd.). When the aqueous dispersion contains a resin other than the fluororesin, the content of the other resin relative to the F particles is preferably 0.1% by volume or more, more preferably 1% by volume or more, and is preferably 15% by volume or less, more preferably 10% by volume or less.
[0039] The aqueous dispersion may contain a surfactant. When the aqueous dispersion contains a surfactant, the surfactant is nonionic, and the hydrophobic portion of the surfactant preferably has an acetylene group or a polysiloxane group, and the hydrophilic portion preferably has an oxyalkylene group or an alcoholic hydroxyl group. That is, when the aqueous dispersion contains a surfactant, a nonionic surfactant is preferred, and a polyoxyalkylene alkyl ether, an acetylene-based surfactant or a silicone-based surfactant is more preferred. When the aqueous dispersion contains a surfactant, the content of the surfactant is preferably 1 to 15% by mass relative to the total mass of the aqueous dispersion, which enhances the affinity between the components and tends to further improve the dispersion stability of the aqueous dispersion. Specific examples of silicone surfactants include "BYK-347", "BYK-349", "BYK-378", "BYK-3450", "BYK-3451", and "BYK-34 55," "BYK-3456" (manufactured by BYK Japan KK), "KF-6011," and "KF-6043" (manufactured by Shin-Etsu Chemical Co., Ltd.).
[0040] Specific examples of polyoxyalkylene alkyl ethers include "Tergitol TMN-100X" (manufactured by The Dow Chemical Company), "Lutensol TO8", "Lutensol XL70", "Lutensol XL80", "Lutensol XL90", "Lutensol XP80", and "Lutensol M5" (all manufactured by BASF), "Newcol 1305", "Newcol 1308FA", and "Newcol 1310" (all manufactured by Nippon Nyukazai Co., Ltd.), "Leocol TDN-90-80", and "Leocol SC-90" (all manufactured by Lion Specialty Chemicals).
[0041] The aqueous dispersion may contain a pH buffering agent, such as carbonic acid, phosphoric acid, boric acid, formic acid, oxalic acid, acetic acid, citric acid, isocitric acid, lactic acid, and ammonium salts thereof, as well as sulfonic acids and amino acids. The content of the pH buffer in the aqueous dispersion is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and even more preferably 0.1% by mass or more, from the viewpoint of effectively suppressing the viscosity change of the aqueous dispersion over time. The content of the pH buffer is preferably 5% by mass or less, more preferably 4% by mass or less, and even more preferably 3% by mass or less.
[0042] The aqueous dispersion may contain at least one nonionic water-soluble polymer selected from the group consisting of polyvinyl alcohol-based polymers, polyvinylpyrrolidone-based polymers, and polysaccharides. In this case, not only the dispersion stability of the aqueous dispersion but also the rheological properties are improved, and the handling properties of the aqueous dispersion, such as film-forming properties, are likely to be further improved. As a result, it is easier to form a thick molded product or a molded product of any shape from the aqueous dispersion. In particular, if the water-soluble polymer has a nonionic hydroxyl group, this tendency is likely to be significant. The polyvinyl alcohol based polymer may be a partially acetylated or partially acetalized polyvinyl alcohol. Polysaccharides include glycogens, amicropectins, dextrins, glucans, fructans, chitins, amyloses, agaroses, amicropectins, and celluloses, including methylcellulose, ethylcellulose, hydroxymethylcellulose, hydroxyethylcellulose, and hydroxypropylcellulose. The nonionic water-soluble polymer is preferably a nonionic polysaccharide, more preferably a nonionic cellulose, and further preferably hydroxymethyl cellulose, hydroxyethyl cellulose, or hydroxypropyl cellulose. Specific examples of such nonionic polysaccharides include the "Sunrose (registered trademark)" series (manufactured by Nippon Paper Industries Co., Ltd.), the "Metolose (registered trademark)" series (manufactured by Shin-Etsu Chemical Co., Ltd.), and "HEC CF Grade" (manufactured by Sumitomo Seika Chemicals Co., Ltd.). When the aqueous dispersion contains a nonionic water-soluble polymer, the content of the nonionic water-soluble polymer is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, based on the total amount of the aqueous dispersion. The content is preferably less than 1% by mass. The ratio of the mass of the water-soluble polymer to the mass of the F particles in the aqueous dispersion is preferably 0.001 or more, more preferably 0.01 or more. The ratio is preferably less than 0.1.
[0043] The aqueous dispersion may further contain additives such as a thixotropic agent, a viscosity adjusting agent (such as a thickener), an antifoaming agent, a dehydrating agent, a plasticizer, a weathering agent, an antioxidant, a heat stabilizer, a lubricant, an antistatic agent, a whitening agent, a colorant, a conductive material, a release agent, a surface treatment agent, a flame retardant, a conductive filler, and a preservative. In one embodiment, the aqueous dispersion preferably contains at least one selected from the group consisting of a surfactant, a thickener, and an aromatic polymer, which allows the liquid properties, such as the surface tension, of the aqueous dispersion to be suitably adjusted.
[0044] The surface tension of the aqueous dispersion is 50 mN / m or less, and from the viewpoint of improving the wettability of the aqueous dispersion, it is preferably 40 mN / m or less. From the viewpoint of suppressing the sedimentation of the F particles and the inorganic filler, the surface tension of the aqueous dispersion is preferably 20 mN / m or more, more preferably 25 mN / m or more. The surface tension of the aqueous dispersion is preferably adjusted by the inclusion of the above-mentioned other components, particularly the inclusion of a surfactant. The viscosity of the aqueous dispersion at 25° C. is preferably 10,000 mPa·s or less, more preferably 3,000 mPa·s or less. The viscosity of the aqueous dispersion at 25° C. is preferably 500 mPa·s or more, more preferably 600 mPa·s or more. The thixotropy ratio of the aqueous dispersion is preferably equal to or less than 6, more preferably equal to or less than 5, and even more preferably equal to or less than 4. The thixotropy ratio of the aqueous dispersion is preferably equal to or more than 1, and more preferably equal to or more than 2. When the thixotropy ratio of the aqueous dispersion is within the above range, the settling of the F particles and the inorganic filler is more easily suppressed. The viscosity or thixotropy of the aqueous dispersion is preferably adjusted by the inclusion of the other components described above, in particular by the inclusion of a water-soluble polymer. The pH of the aqueous dispersion is preferably 4-10, more preferably 7-10, and even more preferably 8-10.
[0045] The aqueous dispersion is obtained by mixing F particles, a high specific gravity inorganic filler, water, and other components as necessary. The order of mixing is not particularly limited, and the mixing method may be either a lump mix or a multiple-part mix.
[0046] Examples of mixing devices for obtaining aqueous dispersions include blade-equipped stirring devices such as a Henschel mixer, a pressure kneader, a Banbury mixer, and a planetary mixer; media-equipped grinding devices such as a ball mill, an attritor, a basket mill, a sand mill, a sand grinder, a Dyno Mill, a Dispermat, an SC Mill, a spike mill, and an agitator mill; and dispersing devices equipped with other mechanisms such as a microfluidizer, a nanomizer, an ultimizer, an ultrasonic homogenizer, a dissolver, a disperser, a high-speed impeller, a thin film swirling high-speed mixer, a planetary stirrer, and a V-type mixer.
[0047] The use of the aqueous dispersion is not particularly limited, and it can be used, for example, for the production of molded products. In particular, the aqueous dispersion is suitable for applications in which it is desired to favorably express the properties of the F polymer contained in the aqueous dispersion.
[0048] The aqueous dispersion is useful as a material for imparting insulating properties, heat resistance, corrosion resistance, chemical resistance, water resistance, impact resistance, and the like. In one embodiment, the aqueous dispersion is preferably used to form a resin layer on the surface of a substrate, for example, a nonwoven fabric sheet. The substrate and the nonwoven fabric sheet will be described later.
[0049] The method for producing the laminate of the present disclosure includes applying the aqueous dispersion of the present disclosure to the surface of a substrate, heating to remove the water, and further heating to melt and sinter the F particles to form a resin layer.
[0050] Examples of the substrate include metal substrates (metal foils of copper, nickel, aluminum, titanium, alloys thereof, and the like), heat-resistant resin films (heat-resistant resin films of polyimide, polyamide, polyetheramide, polyphenylene sulfide, polyaryl ether ketone, polyamideimide, liquid crystalline polyester, tetrafluoroethylene-based polymers, and the like), prepreg substrates (precursors of fiber-reinforced resin substrates), ceramic substrates (ceramic substrates of silicon carbide, aluminum nitride, silicon nitride, and the like), and glass substrates.
[0051] The shape of the substrate may be flat, curved, or uneven, and may be any of foil, plate, film, and fiber (woven fabric, nonwoven fabric, etc.). The ten-point average roughness of the surface of the substrate is preferably 0.01 to 0.05 μm. The ten-point average roughness is measured in accordance with Rzjis of JIS B0601:2013. The surface of the substrate may be surface-treated with a silane coupling agent or plasma-treated. Examples of such silane coupling agents include the same silane coupling agents as those that may be used for surface treatment of inorganic fillers. The peel strength between the resin layer and the substrate is preferably 10 N / cm or more, more preferably 15 N / cm or more, and is preferably 100 N / cm or less.
[0052] In one embodiment, the substrate is preferably a nonwoven sheet. In one embodiment, the nonwoven sheet may contain an inorganic filler, and the inorganic filler may be exposed from the sheet. Examples of the inorganic filler contained in the nonwoven sheet include SiO2 particles. In one embodiment, the nonwoven sheet may contain polytetrafluoroethylene. In one embodiment, the nonwoven sheet may contain an inorganic filler (particularly SiO2 particles) and polytetrafluoroethylene. Since SiO2 particles have a low dielectric loss tangent and low linear expansion, the linear expansion of the substrate can be suppressed by mixing them with polytetrafluoroethylene, and the dielectric loss tangent can be suppressed low. The aqueous dispersion of the present disclosure can form a resin layer with excellent adhesiveness, so even if the substrate is a nonwoven sheet of each of the above-mentioned embodiments, the resin layer can be suitably formed.In addition, even if the nonwoven sheet contains SiO2 particles with high water repellency, the aqueous dispersion of the present disclosure has a suitable wettability, so that the adhesiveness between layers is guaranteed when a resin layer is formed on the sheet, and the aqueous dispersion does not soak into the sheet too much, so that the desired physical properties can be maintained.
[0053] Examples of the method for applying the aqueous dispersion include a coating method, a droplet discharging method, and a dipping method, and preferably a roll coating method, a knife coating method, a bar coating method, a die coating method, or a spray method. Heating for removing water is preferably performed at 100 to 200°C for 0.1 to 30 minutes. In this heating, it is not necessary to completely remove water, but it is sufficient to remove water to the extent that the layer formed by packing of the F particles and the inorganic filler can maintain a self-supporting film. In addition, when heating, air may be blown to promote removal of water by air drying. The heating for calcining the F polymer is preferably carried out at a temperature equal to or higher than the calcination temperature of the F polymer, more preferably at 360 to 400° C. for 0.1 to 30 minutes. The heating device for each heating may be an oven or a ventilation drying furnace. The heat source in the device may be a contact type heat source (hot air, hot plate, etc.) or a non-contact type heat source (infrared radiation, etc.). The wire may be a conductive material. The heating may be carried out under normal pressure or under reduced pressure. The atmosphere during each heating may be either an air atmosphere or an inert gas atmosphere (helium gas, neon gas, argon gas, nitrogen gas, etc.).
[0054] The resin layer is formed through the steps of applying an aqueous dispersion and heating. These steps may be performed once each, or may be repeated two or more times. For example, an aqueous dispersion may be applied to the surface of a substrate and heated to form a resin layer, and an aqueous dispersion may be applied to the surface of the resin layer and heated to form a second resin layer. In addition, at the stage where an aqueous dispersion is applied to the surface of a substrate and heated to remove water, an aqueous dispersion may be applied to the surface and heated to form a resin layer. The aqueous dispersion may be applied to only one surface of the substrate, or may be applied to both surfaces of the substrate. In the former case, a laminate having a substrate layer and a resin layer on one surface of the substrate layer is obtained, and in the latter case, a laminate having a substrate layer and resin layers on both surfaces of the substrate layer is obtained.
[0055] The thickness of the resin layer can be appropriately selected according to the application, and may be, for example, 5 μm or more, or 10 μm or more. The thickness of the resin layer may be 200 μm or less, 150 μm or less, or 100 μm or less. Since the aqueous dispersion of the present disclosure is easy to form a uniform resin layer even with a thin thickness and is unlikely to cause defects, the thickness of the resin layer may be 20 μm or less, or 15 μm or less.
[0056] Suitable specific examples of the laminate include a metal-clad laminate having a metal foil and a resin layer on at least one surface of the metal foil, and a multilayer film having a polyimide film and a resin layer on both surfaces of the polyimide film.
[0057] Laminates formed from aqueous dispersions are useful as antenna parts, printed circuit boards, aircraft parts, automobile parts, sporting goods, food industry products, heat dissipation parts, and the like. Specifically, these include electric wire coating materials (aircraft electric wires, etc.), enameled wire coating materials used in motors for electric vehicles, etc., electrical insulating tape, insulating tape for oil drilling, oil transport hoses, hydrogen tanks, materials for printed circuit boards, separation membranes (microfiltration membranes, ultrafiltration membranes, reverse osmosis membranes, ion exchange membranes, dialysis membranes, gas separation membranes, etc.), electrode binders (for lithium secondary batteries, for fuel cells, etc.), copy rolls, furniture, automobile dashboards, covers for home appliances, etc., sliding parts (load bearings, yaw bearings, sliding shafts, valves, bearings, bushings, seals, thrust washers, wear rings, etc.), and other applications. They are useful as: tools, pistons, slide switches, gears, cams, conveyor belts, food transport belts, etc.), tension ropes, wear pads, wear strips, tube lamps, test sockets, wafer guides, wear parts of centrifugal pumps, chemical and water supply pumps, tools (shovels, files, hacksaws, etc.), boilers, hoppers, pipes, ovens, baking molds, chutes, racket strings, dies, toilets, container coating materials, heat dissipation boards mounted for power devices, heat dissipation members for wireless communication devices, transistors, thyristors, rectifiers, transformers, power MOS FETs, CPUs, heat dissipation fins, metal heat sinks, blades for windmills, wind power generation equipment, aircraft, etc., housings for personal computers and displays, electronic device materials, interior and exterior parts of automobiles, sealing materials for processing machines and vacuum ovens that perform heat treatment under low oxygen conditions, plasma processing equipment, heat dissipation parts in processing units for sputtering and various dry etching equipment, electromagnetic wave shielding, etc.
[0058] Laminates formed from the aqueous dispersion are useful as electronic substrate materials such as flexible printed wiring boards and rigid printed wiring boards, protective films and heat dissipating substrates, particularly heat dissipating substrates for automobiles.
[0059] In one embodiment of the present disclosure, a laminate produced by the above-described method for producing a laminate is provided. In a further embodiment of the present disclosure, there is provided a laminate comprising a layer S containing polytetrafluoroethylene and an inorganic filler and a layer T containing an F polymer and a high specific gravity inorganic filler, wherein the ratio of the thickness of layer S to the thickness of layer T is 2 to 50, and the total thickness is 50 to 500 μm. Hereinafter, the laminate in this embodiment will also be referred to as "laminate A". Note that, when a plurality of layers T and / or layers S are present in laminate A, the ratio of the total thickness of each layer is within the above range. The laminate A may be manufactured by the above-mentioned manufacturing method of a laminate, using layer S as a base material.
[0060] When a printed circuit board material is processed or applied to an antenna element or the like, it is preferable to be able to adjust the electrical properties of the material as desired in order to obtain a printed circuit board with lower transmission loss. For example, it is desirable to be able to adjust the dielectric constant, particularly in the thickness direction, to any range while maintaining the low dielectric tangent of the material. As a method for obtaining such a material, a method of adjusting the electrical properties of the material by combining a material having a low dielectric tangent with a ferroelectric material is considered. However, in the conventional method, it is difficult to control the dielectric constant and dielectric tangent, and in addition, it is difficult to simultaneously satisfy physical properties such as adhesion to the substrate. On the other hand, according to the configuration of the laminate A, for example, the dielectric constant and dielectric tangent can be controlled by laminating a layer S having a low dielectric tangent and a layer T having a moderate dielectric constant, and adjusting the lamination style and thickness.
[0061] Details of the F polymer and the high-density inorganic filler in the layer T are as described above in the section "Aqueous Dispersion." The high-density inorganic filler in the layer T is preferably TiO2 particles. In the layer T, the mass ratio of the high-density inorganic filler to the F polymer is preferably less than 1, and from the viewpoint of dispersibility of the high-density inorganic filler, it is more preferably 0.8 or less, and even more preferably 0.6 or less. From the viewpoint of satisfactorily exhibiting the properties of the high-density inorganic filler, such as dielectric constant, the mass ratio of the high-density inorganic filler to the total mass of the F particles is preferably 0.1 or more, and more preferably 0.2 or more.
[0062] The thickness of the layer T may be 5 μm or more, or 10 μm or more. The thickness of the layer T may be 200 μm or less, 150 μm or less, 100 μm or less, 20 μm or less, or 15 μm or less. When the laminate A has a plurality of layers T, the total thickness of the layers T may be in the above range. The layer T may be a resin layer formed by heating the aqueous dispersion of the present disclosure and then further heating it to melt and sinter the F particles, as described above in the section "Method for producing a laminate."
[0063] The inorganic filler in layer S may be the high-density inorganic filler described above in the section "Aqueous dispersion liquid" and an inorganic filler other than the high-density inorganic filler. A filler different from the high-density inorganic filler in layer T is preferable, and SiO2 particles are more preferable. The layer S may be a nonwoven sheet containing an inorganic filler and polytetrafluoroethylene, as described above as the substrate in the section "Method of Manufacturing the Laminate." The thickness of the layer S may be 50 μm or more, 75 μm or more, or 100 μm or more. The thickness of the layer T may be 1000 μm or less, 500 μm or less, or 250 μm or less. When the laminate A has a plurality of layers S, the total thickness of the layers S may be in the above range.
[0064] In one embodiment, it is preferred that the inorganic filler in layer S is SiO2 particles, and the high specific gravity inorganic filler in layer T is TiO2 particles. In one embodiment, the average particle size of the inorganic filler in the layer S is preferably larger than the average particle size of the inorganic filler in the layer T. According to this embodiment, the adhesion at the interface between the layer S and the layer T is improved.
[0065] In the laminate A, the number and arrangement of the layer T and the layer S are not particularly limited. For example, the laminate A may be formed by laminating one layer each of the layer T and the layer S, or may be formed by providing a plurality of layers T and / or layers S. More specifically, for example, the laminate A may include a layer S, a layer T, and a layer S in this order, or a layer T, a layer S, and a layer T in this order.
[0066] The ratio of the thickness of the layer S to the thickness of the layer T is 2 to 50, may be 2 to 40, or may be 2 to 30. When the ratio is within the above range, the characteristics of the layer S (for example, low dielectric tangent and low linear expansion when the layer S contains SiO2 particles) can be adequately imparted to the layer T (for example, ferroelectricity when the layer T contains TiO2 particles).
[0067] The total thickness of the laminate A may be 50 to 500 μm, 75 to 500 μm, or 100 to 500 μm. The total thickness of the laminate A is the thickness of the entire laminate A.
[0068] FIG. 1 shows a schematic diagram of an example of the laminate A. The laminate A (10) comprises a first layer T (T1), a layer S (S), and a second layer T (T2) in this order. The first and second layers T (T1, T2) contain F polymer and TiO2 particles, and the layer S (S) contains polytetrafluoroethylene and SiO2 particles. By appropriately adjusting the thickness of the layer T (i.e., the total thickness of the first layer T (T1) and the second layer T (T2)) within a range in which the ratio of the thickness of the layer S to the thickness of the layer T is 2 to 50, the low dielectric tangent of the layer S and the dielectric property of the layer T can be adjusted, and a laminate having desired electrical properties can be produced. However, the laminate is not limited to the above embodiment.
[0069] The metal clad laminate in one embodiment of the present disclosure includes the above-mentioned laminate A and a metal layer. The metal layer may be a metal layer formed of gold, silver, copper, iron, nickel, aluminum, or an alloy metal thereof. The metal clad laminate is preferably a copper clad laminate.
[0070] The metal clad laminate can be produced by various methods including known methods, such as a method of depositing a metal layer on the laminate A, a method of forming a metal layer by electroless plating or electrolytic plating, a method of overlapping a metal foil with the laminate A and thermocompression bonding, and the like.
[0071] The circuit board according to an embodiment of the present disclosure includes a laminate A and a conductor layer. The form of the circuit board is not particularly limited as long as it includes the laminate A and the conductor layer. The circuit board may be a circuit board having a circuit pattern formed on the metal layer of the metal clad laminate. The conductor layer may be made of a conductive metal such as gold, silver, copper, iron, nickel, aluminum, or an alloy metal thereof.
[0072] The use of the circuit board is not particularly limited, and the circuit board may be used as a transmission line (coaxial line, strip line, microstrip line, coplanar line, parallel line, etc.), an antenna (microwave or millimeter wave antenna), an antenna device in which an antenna and a transmission line are integrated, etc. Examples of antennas include antennas that utilize millimeter waves or microwaves, such as a waveguide slot antenna, a horn antenna, a lens antenna, a printed antenna, a triplate antenna, a microstrip antenna, and a patch antenna. In one embodiment, the circuit board is preferably used in various sensors (such as an on-vehicle radar).
[0073] The automotive radar according to the embodiment of the present disclosure includes a circuit board including a laminate A and a conductor layer. The details of the circuit board are as described above. The laminate A can control the dielectric constant and dielectric tangent, for example, by laminating a layer S having a low dielectric tangent and a layer T having a high dielectric constant, and therefore can be suitably applied to an on-board radar in which adjustment of such electrical characteristics is desired. EXAMPLES
[0074] Next, the embodiments of the present disclosure will be specifically described using examples, but the embodiments of the present disclosure are not limited to these examples.
[0075] The liquid properties of the aqueous dispersion were determined by the following measuring methods. <Surface tension> The measurement is performed using a surface tensiometer at 25°C by the Wilhelmy method. <Viscosity> It is measured using a Brookfield viscometer at 25°C and 30 rpm. The measurement is repeated three times and the average value of the three measurements is calculated. <Thixotropy ratio> The thixotropy ratio is calculated by dividing the viscosity η1 measured at a rotation speed of 30 rpm of the aqueous dispersion by the viscosity η2 measured at a rotation speed of 60 rpm. Each viscosity measurement is repeated three times, and the average value of the three measured values is calculated.
[0076] The physical properties of the layer and the laminate were evaluated by the following measuring methods. <Layer thickness> Using a thickness gauge (model: H-type 2.4N, manufacturer: PEACOCK Company), eight points were measured: the four corners of the measurement sample and four points 1 cm away from the edges and the center of the four sides. The thickness of these eight points was then measured and the average value was calculated. <Peel strength> The resin layer and copper foil were peeled from one end of a double-sided copper-clad laminate cut into a rectangle (100 mm long, 10 mm wide) to a position 50 mm from one end in the longitudinal direction, and the peeling was performed at a 90-degree angle with the same position as the center at a pulling speed of 50 mm / min. The maximum load was recorded as the peel strength (N / 10 mm). A higher peel strength indicates better interlayer adhesion of the double-sided copper-clad laminate. <Dielectric constant> According to the SPDR test method, a sheet sample cut to 50 x 50 mm from a double-sided copper-clad laminate was placed on a resonant cavity fixture and connected to a Detech PNA network analyzer N5225B to measure and determine the relative dielectric constant at a frequency of 20 GHz. <Dielectric tangent> According to the SPDR test method, a sheet sample cut to 50 x 50 mm from a double-sided copper-clad laminate was placed on a resonant cavity fixture and connected to a Detech PNA network analyzer N5225B to measure and determine the dielectric loss tangent at a frequency of 20 GHz.
[0077] (Example 1) The F particles contain 97.9 mol% of TFE units, 0.1 mol% of NAH units, and 2.0 mol% of PPVE units, in that order, and have a carbonyl group-containing group with a main chain carbon number of 1×10 6 Particles (D50: 2.1 μm) of tetrafluoroethylene polymer (melting temperature: 300° C.) with 1000 particles per particle were used, and TiO2 particles (average particle size: 0.2 μm, specific gravity: 4.3) were used as high specific gravity inorganic filler. The components were mixed so that the F particles were 25 mass%, the TiO2 particles were 15 mass%, and the water was 60 mass%, and then sheared to prepare the aqueous dispersion of Example 1. In the preparation, a silicone surfactant and polyacrylic acid were added to adjust the surface tension of the aqueous dispersion to 30 mN / m, the viscosity at 25°C to 3000 mPa s, and the thixotropy ratio to 1.2.
[0078] (Example 2) An aqueous dispersion of Example 2 was prepared in the same manner as in Example 1, except that the components were mixed so that the F particles were 20 mass%, the TiO2 particles were 20 mass%, and the water was 60 mass%. At this time, the aqueous dispersion was adjusted to have a surface tension of 33 mN / m, a viscosity at 25°C of 4000 mPa s, and a thixotropic ratio of 1.3.
[0079] (Example 3) An aqueous dispersion of Example 3 was prepared in the same manner as in Example 1, except that TiO2 particles having an average particle size of 10 μm were used instead of the TiO2 particles of Example 1. At this time, the aqueous dispersion was adjusted to have a surface tension of 27 mN / m, a viscosity at 25°C of 2000 mPa s, and a thixotropic ratio of 1.1.
[0080] (Example 4) Except for adjusting the amount of silicone surfactant added, the aqueous dispersion of Example 4 was prepared in the same manner as in Example 1. At this time, the surface tension of the aqueous dispersion was adjusted to 55 mN / m, the viscosity at 25°C to 4000 mPa s, and the thixotropy ratio to 4.5.
[0081] In Examples 1 to 4, the total content of the silicone surfactant and polyacrylic acid was 3% by mass or less of the aqueous dispersion.
[0082] <Preparation of copper clad laminate> The aqueous dispersions of Examples 1 to 4 were applied to one side of a copper foil (thickness: 12 μm), heated at 150°C for 5 minutes, and then baked at 350°C for an additional 3 minutes to obtain a laminate comprising a copper foil layer and a resin layer (thickness: 9 μm) containing a tetrafluoroethylene-based polymer and TiO2 particles. Two laminates were placed facing each other with the resin layer sides facing each other, and a base sheet (thickness: 100 μm) consisting of 60 mass% silica and 40 mass% polytetrafluoroethylene was sandwiched between them. They were then hot-pressed at a temperature of 350°C and a bonding pressure of 2 MPa for 2 minutes to obtain a double-sided copper-clad laminate having a copper foil layer, a resin layer, a base sheet layer, a resin layer, and a copper foil layer in that order. The peel strength, dielectric loss tangent, and dielectric constant of the double-sided copper-clad laminates obtained from each aqueous dispersion were measured, and the results are summarized in Table 1. Note that the dielectric loss tangent and dielectric constant of the double-sided copper-clad laminates obtained from the aqueous dispersions of Examples 3 and 4 were not measured because the peel strength was low. In addition, in a double-sided copper-clad laminate formed from an aqueous dispersion prepared in the same manner as in Example 1 except that it did not contain TiO2 particles, the dielectric tangent, relative dielectric constant, and peel strength were 0.0002, 2.1, and 10 or more, respectively.
[0083] [Table 1] [Explanation of symbols]
[0084] 10 Laminate S layer S T1 layer T T2 layer T
Claims
1. The aqueous dispersion contains particles of a heat-fusible tetrafluoroethylene-based polymer in an amount of 10% by mass or more relative to the aqueous dispersion, an inorganic filler having an average particle size of less than 10 μm and a specific gravity of 3.0 or more, and water, wherein the mass ratio of the inorganic filler to the particles of the heat-fusible tetrafluoroethylene-based polymer is less than 1, and the aqueous dispersion has a surface tension of 50 mN / m or less.
2. 2. The aqueous dispersion according to claim 1, wherein the heat-fusible tetrafluoroethylene-based polymer comprises a unit based on tetrafluoroethylene and at least one of a unit based on perfluoro(alkyl vinyl ether) and a unit based on hexafluoropropylene.
3. The inorganic filler is TiO 2 The aqueous dispersion according to claim 1 , which is in the form of particles.
4. 2. The aqueous dispersion according to claim 1, having a viscosity at 25°C of 10,000 mPa·s or less.
5. Viscosity η measured at a rotation speed of 30 rpm 1 The viscosity η measured at a rotation speed of 60 rpm 2 The aqueous dispersion according to claim 1 , wherein the aqueous dispersion has a thixotropy ratio calculated by dividing the thixotropy ratio by 1 / 2, which is 6 or less.
6. A method for producing a laminate, comprising applying the aqueous dispersion according to any one of claims 1 to 5 to a surface of a substrate, heating to remove the water, and further heating to melt and sinter the particles of the heat-fusible tetrafluoroethylene-based polymer to form a resin layer.
7. The method for producing a laminate according to claim 6, wherein the resin layer has a thickness of 20 μm or less.
8. The method for producing a laminate according to claim 6 , wherein the substrate is a nonwoven fabric sheet.
9. The method for producing a laminate according to claim 8 , wherein the nonwoven sheet comprises polytetrafluoroethylene.
10. The nonwoven sheet contains an inorganic filler, and the inorganic filler is SiO 2 The method for producing a laminate according to claim 9 , which comprises particles.
11. A laminate comprising: a layer S containing polytetrafluoroethylene and an inorganic filler; and a layer T containing a heat-fusible tetrafluoroethylene-based polymer and an inorganic filler having an average particle size of less than 10 μm and a specific gravity of 3.0 or more, wherein the ratio of the thickness of the layer S to the thickness of the layer T is 2 to 50, and the total thickness is 50 to 500 μm.
12. The inorganic filler in the layer S is SiO 2 particles, and the inorganic filler in the layer T is TiO 2 The laminate of claim 11 which is a particle.
13. The laminate according to claim 11 , wherein the average particle size of the inorganic filler in the layer S is larger than the average particle size of the inorganic filler in the layer T.
14. A metal clad laminate comprising the laminate according to any one of claims 11 to 13 and a metal layer.
15. An on-vehicle radar comprising a circuit board including the laminate according to any one of claims 11 to 13 and a conductor layer.
Citation Information
Patent Citations
Resin composition, metal laminate and printed circuit board using the same, and method for manufacturing the metal laminate
JP2022514976A
Dielectric material and flexible copper clad laminate including the same
JP2023002495A